Effects of COVID-19 Related Lockdowns on Agricultural Markets in India: Phone Survey Data From Wheat and Tomato Farmers in Haryana - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
These data are from phone surveys conducted for 1,767 wheat and tomato farmers spread across four districts in the state of Haryana, India. These surveys were conducted by phone during the harvest of the Rabi (winter) crop of 2020 in the context of an ongoing panel survey on agricultural risk management and coincided with the imposition of COVID-19 related lockdown in India. In the case of wheat farmers, the phone surveys were conducted between April and May 2020 and included a series of questions related to the effects of the lockdown on crop losses, harvesting practices, harvest costs, and commercialization of produce after harvest. In the case of tomato, a multi-picking crop, we administered the same set of questions through several follow-up surveys over the course of the harvesting season from June to July 2020, allowing us to explore the dynamic effects of the lockdown restrictions. In addition, for both wheat and tomato producers, the survey asked about borrowing and included a short module on household’s access to food before and after the lockdown, providing insights on lockdown-related borrowing and disruptions in food security. These datasets provide insight into the effects of lockdown on different phases of production and marketing and the linkages between agricultural income losses and risk coping mechanisms. These datasets consist of:(1) one wheat farmer survey; (2) six tomato farmer surveys, including 4 weekly surveys and a first and last survey; and (3) one dataset presenting select data from earlier rounds of data collection.